2016
DOI: 10.3847/0004-6256/151/6/167
|View full text |Cite
|
Sign up to set email alerts
|

The Araucaria Project: On the Tip of the Red Giant Branch Distance Determination to the Magellanic Clouds

Abstract: We present a precise optical and near-infrared determination of the tip of the red giant branch (TRGB) brightness in the Large and Small Magellanic Clouds (respectively, LMC and SMC). The commonly used calibrations of the absolute magnitude of the TRGB lead to an overestimation of the distance to the LMC and SMC in the K band, and an underestimation of the distance in the optical I band for both galaxies. Reported discrepancies are at the level of 0.2 mag, with respect to the very accurate distance determinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…In an earlier study, Jang and Lee [17] used ten fields of OGLE-III stars in the LMC and found I TRGB 0 ¼14.485AE 0.030, which already includes their estimate of extinction A I of around 0.1 mag on average. Another determination based on OGLE-III data was performed by Górski et al [29], who used 17 fields and found I TRGB ¼ 14.62 AE 0.03, compatible with Eq. (6) within stated uncertainties.…”
Section: B Large Magellanic Cloudmentioning
confidence: 54%
“…In an earlier study, Jang and Lee [17] used ten fields of OGLE-III stars in the LMC and found I TRGB 0 ¼14.485AE 0.030, which already includes their estimate of extinction A I of around 0.1 mag on average. Another determination based on OGLE-III data was performed by Górski et al [29], who used 17 fields and found I TRGB ¼ 14.62 AE 0.03, compatible with Eq. (6) within stated uncertainties.…”
Section: B Large Magellanic Cloudmentioning
confidence: 54%
“…Table 1 presents the measured values of the TRGB in the I, V, J and K bands for the selected fields. The TRGB measurements with the Sobel filter are not given in this paper, however they have been reported for the most of the fields earlier by Górski et al (2016).…”
Section: Trgb Measurement In the Lmc And Smcmentioning
confidence: 99%
“…Finally we obtain the zero-points of the TRGB: M QT,T RGB = −4.004 ± 0.096 mag for the QT calibration and M I,T RGB = −3.970 ± 0.102 mag for the blue I calibration. Quoted uncertainties, 0.096 mag and 0.102 mag, are derived as summarized in Table 4: TRGB detection errors (0.020 mag and 0.042 mag), an extinction correction error (0.07 mag (Haschke et al 2011;Górski et al 2016)), a photometric zero-point error (0.03 mag), the QT transformation error (0.014 mag), and the LMC distance error (0.049 mag). The systematic uncertainty is dominated by the extinction error and the LMC distance error.…”
Section: The Large Magellanic Cloud As a Distance Anchormentioning
confidence: 99%